Changes in the depth habitat of the Oligocene planktic foraminifera (Dentoglobigerina venezuelana) induced by thermocline deepening in the eastern equatorial Pacific. (15th June 2016) - Matsui, Hiroki; Nishi, Hiroshi; Takashima, Reishi; Kuroyanagi, Azumi; Ikehara, Minoru; Takayanagi, Hideko; Iryu, Yasufumi
Abstract: Understanding planktic foraminiferal depth habitat along with consistent taxonomic concepts is key to accurate reconstruction of paleoceanographic records. The Oligocene‐Pliocene long‐ranging and widely distributed species Dentoglobigerina venezuelana lived in the mixed layer (shallower) during the early Oligocene, whereas the same species calcified at thermocline or subthermocline depths (deeper) during the late Oligocene and Miocene. The exact timing of the species' depth habitat change and its possible relationships with Oligocene climate dynamics remain unknown. Here we reveal isotopic records of D. venezuelana along with the Paragloborotalia siakensis group (a mixed‐layer dweller) by using sediments at Integrated Ocean Drilling Program Site U1334 in the eastern equatorial Pacific throughout the Oligocene. A two‐step depth habitat change of D. venezuelana is apparent: (1) from upper to lower mixed layer (~27.4 Ma) and (2) from lower mixed layer to thermocline depth (~26.3 Ma). In addition, the planktic foraminiferal faunal assemblage experienced a marked change from dominantly thermocline (deeper) species to abundant mixed‐layer (shallower) species, suggesting that depth habitat shifts of D. venezuelana were clearly related to thermocline deepening in the eastern equatorial Pacific. Comparison of the first isotopic shift (~27.4 Ma) at multiple sites (U1334, U1333, and 1218) revealed a southward depth habitat change of D. venezuelana within ~200 kyr, implying overall thermocline deepening with reduced steepness in the eastern equatorial Pacific. We consider that global warming conditions during the late Oligocene likely caused thermocline deepening with upwelling decrease in the eastern equatorial Pacific, guiding D. venezuelana to adapt to greater depths in the water column. Key Points: Deeper adaptation of Dentoglobigerina venezuelana occurred in the late Oligocene The eastern equatorial Pacific thermocline deepened in tandem with these depth habitat changes Warming during the late Oligocene likely caused deepening of the thermocline